2021
DOI: 10.1021/acs.langmuir.1c01009
|View full text |Cite
|
Sign up to set email alerts
|

An Interface Optimization Strategy for g-C3N4-Based S-Scheme Heterojunction Photocatalysts

Abstract: Graphitic carbon nitride (CN) has attracted much attention in photocatalytic fields due to its unique electronic band structure. However, the rapid recombination of photogenerated carriers severely inhibits its catalytic activity. The heterojunction structure has been widely confirmed to significantly improve the photocatalytic activity of CN through the formed interface structure. However, researchers often give attention to the band matching and conductivity of the cocatalyst, while the importance of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Nitrogen (N 2 ) physisorption desorption tests were performed on pure BiOBr and 1.0 AgBr/BiOBr, as shown in Figure d. Both of them have type IV hysteresis loops, indicating the presence of mesoporous structures . An abundant pore structure is conducive to the refraction of light during the photocatalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen (N 2 ) physisorption desorption tests were performed on pure BiOBr and 1.0 AgBr/BiOBr, as shown in Figure d. Both of them have type IV hysteresis loops, indicating the presence of mesoporous structures . An abundant pore structure is conducive to the refraction of light during the photocatalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the interfacial contact can also be moderated to reduce interface contact resistance and facilitate charge migration and separation. 154 3.2.4 Other heterostructures. When n-type CN is in contact with a p-type semiconductor, the electrons will transfer from CN to the p-type semiconductor, resulting in an upward band bending of CN and a downward band bending of the p-type counterpart.…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…Moreover, the interfacial contact can also be moderated to reduce interface contact resistance and facilitate charge migration and separation. 154…”
Section: Various 2d Materials Based Heterostructuresmentioning
confidence: 99%
“…Thanks to the above interesting properties, the WO 3 /g-C 3 N 4 heterostructure was used as a direct solid-state Z-scheme heterojunction that is coupled by two suitable semiconductors to decompose sulfamethoxazole, methylene blue, and 4-chlorophenol in wastewater under visible light. , Recently, Fu et al reported that the coupling of WO 3 /g-C 3 N 4 created an efficient step-scheme (S-scheme) structure photocatalyst favorable for visible-light-driven hydrogen production . The S-scheme has more advantages compared to the Z-scheme, which directs the transfer of charge carriers at the heterojunctions of the two-component semiconductors via the internal electric field direction, the bending band edge, and the Coulomb force interaction. Literature studies indicate that the energy band structure of WO 3 is suitable to establish a Z-scheme photocatalyst with g-C 3 N 4 . , This heterojunction will inhibit the electron–hole recombination rate, leading to the formation of active radicals to prevent the conversion of NO to NO 2 for the WO 3 /g-C 3 N 4 system.…”
Section: Introductionmentioning
confidence: 99%